Irenaeus on creation : the cosmic Christ and the saga of redemption - Steenberg, Irenaeus M. C. 1978- (Vigiliae Christianae, Supplements, 2008)
Scholarship on Irenaeus has long acknowledged the centrality of creation to his theology, yet without fitting this theme securely into the Christological vision of Christ the 'Recapitulator'. Studies have considered elements of Irenaeus' cosmology and anthropology in extraction; but without seeing creation as an intrinsic part of his Christocentric vision, these have only partially been able to capture the intricacy and significance of his embrace of the creation saga. Drawing on the most recent Irenaean scholarship, the present volume explores in detail the Christocentric cosmology of one of the second century's greatest writers, setting him in the context of the theological currents of his day. The result is a volume that offers new insights into the trinitarian articulation of early Christianity, the full significance of humanity as bearing God's 'image', and a fuller reading of the details behind the title, 'Irenaeus the creationist'.